Constitution and Political Ethics: Finding Common Ground - Yunus, Nur Rohim (ADALAH, 2023)
The Constitution and Political Ethics Essay: Finding Common Ground discusses the relationship between the Constitution as the highest law in a country and political ethics as the moral foundation in government. This essay highlights the importance of balancing objective legal principles and ethical values that can maintain political integrity and justice in national life. Several recommendations include preparing a constitution based on universal values, increasing political education based on ethics, and strengthening political ethics monitoring institutions. In addition, integrating ethics into the legal system, public participation in politics, and applying sanctions for ethical violations are crucial steps in maintaining political morality. By building a political culture based on honesty and responsibility, it is hoped that the constitution will be a legal tool and reflect ethical values that guarantee a just and democratic government.